2012
DOI: 10.1111/j.1442-200x.2012.03605.x
|View full text |Cite
|
Sign up to set email alerts
|

Birth by cesarean section is associated with elevated neonatal plasma levels of dimethylarginines

Abstract: ADMA level falls after both vaginal and cesarean birth, whereas SDMA level does not. The higher ADMA level after cesarean birth compared with vaginal birth may contribute to decreased nitric oxide production and bioavailability in neonatal vascular beds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…In late pregnancy, physiologically increased ADMA levels thus help prepare the uterine muscle fibers for the higher contractile activity that is necessary for successful delivery by antagonizing NO-induced uterine relaxation. This is reflected by the higher ADMA level after cesarean birth compared with vaginal birth [36]. After birth, ADMA levels fall, which may contribute to decreased NO production and bioavailability in neonatal vascular beds [36].…”
Section: Roles Of No and Adma In Normal Pregnanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…In late pregnancy, physiologically increased ADMA levels thus help prepare the uterine muscle fibers for the higher contractile activity that is necessary for successful delivery by antagonizing NO-induced uterine relaxation. This is reflected by the higher ADMA level after cesarean birth compared with vaginal birth [36]. After birth, ADMA levels fall, which may contribute to decreased NO production and bioavailability in neonatal vascular beds [36].…”
Section: Roles Of No and Adma In Normal Pregnanciesmentioning
confidence: 99%
“…This is reflected by the higher ADMA level after cesarean birth compared with vaginal birth [36]. After birth, ADMA levels fall, which may contribute to decreased NO production and bioavailability in neonatal vascular beds [36]. …”
Section: Roles Of No and Adma In Normal Pregnanciesmentioning
confidence: 99%
“…Moreover, the list of clinical entities in which altered ADMA levels are found in the pediatric population continues to grow and includes conditions such as hypertension, hypercholesterolemia, chronic kidney disease or diabetes mellitus (see [ 17 ] for review). However, the information on dimethylarginines in the peri-/neonatal period is much scarce [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Herein, we analyzed the plasma concentrations of ADMA, SDMA, l -arginine, and citrulline in a cohort of 130 VLBW preterm infants.…”
Section: Resultsmentioning
confidence: 99%
“…There was no difference between the two groups in terms of hemoglobin values in our study. The study by Vida et al found that levels of asymmetric dimethylarginine were increased in the samples taken from the umbilical vein and artery and from peripheral vein on day 30, with an associated decrease in the production and bioavailability of nitric oxide, and concluded that CS may cause endothelial dysfunction as a result of this, highlighting the need for further studies concerning this issue 23 . It was reported that systemic endothelial function is more closely correlated with the progression of preclinical carotid artery disease, and endothelial function is more closely correlated with carotid IMT than with conventional risk factors 24 .…”
Section: Discussionmentioning
confidence: 99%